Analysis of the whole implementation process and optimization of a Nitinol superelastic stent. Issue 1 (15th January 2019) - Wang, X. M.; Liu, P.; Liang, H.; Zhang, M. C.; Li, L.; Yue, Z. F.
Abstract: Nitinol superelastic stents have been widely used to treat the vascular stenosis due to its excellent mechanical behavior and biocompatibility. However, there exist conflicts between the functional properties and mechanical properties of the stent. An optimization method has been employed to deal with the conflictions with the consideration of the whole implementation process of the stent in this paper. A straight vascular with tumor inside is considered. A commonly used NiTinol superleastic stent with diamond shape strut is employed. The vascular wall tissue and stenotic plaque are also treated as hyperelastic materials. Softwares Isight, ABAQUS and Solidworks are utilized to perform the optimization job. It can be seen that the stresses are high at the areas around the fillets of the stent due to the stress concentration from a primary analysis. Therefore, the two fillets radius, thickness and radius of the stent are chosen as four optimization variables. The optimization object is to decrease the maximum stress of stent and increase the displacement of the plaque. After the optimization, the maximum stress can be decreased by 8.2 %, which implies that the stent's work life can be increased. The stenosis of the blood vessel can be decreased from 56 % to 40.0 %.